2013
DOI: 10.1063/1.4802243
|View full text |Cite
|
Sign up to set email alerts
|

Non-aqueous energy storage devices using graphene nanosheets synthesized by green route

Abstract: In this paper we report the use of triethylene glycol reduced graphene oxide (TRGO) as an electrode material for non-aqueous energy storage devices such as supercapacitors and Li-ion batteries. TRGO based non–aqueous symmetric supercapacitor is constructed and shown to deliver maximum energy and power densities of 60.4 Wh kg–1 and 0.15 kW kg–1, respectively. More importantly, symmetric supercapacitor shows an extraordinary cycleability (5000 cycles) with over 80% of capacitance retention. In addition, Li-stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…As per energy storage mechanism, both anions (PF 6 − ) and cations (Li + ) are adsorbed on the graphene sheets during charging process, whereas the process is reversed during discharge. 5 It is obvious to notice that increasing sweep rate leads to a decrease in the net charge under the curve. At the high scan rates the surface of the active material (RGO) is only involved in the electrochemical reaction rather than the bulk, which results in a decrease in specific capacitance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As per energy storage mechanism, both anions (PF 6 − ) and cations (Li + ) are adsorbed on the graphene sheets during charging process, whereas the process is reversed during discharge. 5 It is obvious to notice that increasing sweep rate leads to a decrease in the net charge under the curve. At the high scan rates the surface of the active material (RGO) is only involved in the electrochemical reaction rather than the bulk, which results in a decrease in specific capacitance.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained values are highly comparable to the previous reports. 5,16,17 Recently, Mhamane et al, reported the capacitance of 97 F g −1 at a current density of 0.1 A g −1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3.34 and Table 3.4 summarize specific capacitances of common materials for supercapacitor applications [34]. Because of their merits of a large, open, flat layer with high surface area and excellent electronic transport properties, GNSs have been considered a promising electrode material for supercapacitors [34][35][36][37][38][39][40]. The capacitance of graphene can approach ∼200 F g −1 [34,35], even though the specific surface area of graphene is not high compared to activated carbon.…”
Section: Graphene For Supercapacitorsmentioning
confidence: 99%